Academicians' Perceptions on Their Profession. (13th May 2015) - Erus, Seher Merve; Cakmak, Esra; Celebi, Cigdem Demir
Abstract: In recent years, knowledge-based society and economic structures have changed the academicians' responsibilities, assignments, work definitions, activities they participate and sufficiency. Therefore it is thought that these changes affect "academicianship" concept in Turkey. In this context, the object of this study is to determine academicians' perceptions on their professions. Content analysis, which is one of the qualitative research approaches, is used in the study. Data were collected from 81 academicians working at universities in Istanbul via open-ended questionnaire form, which includes three themes: (i) advantages of their profession, (ii) disadvantages of their professions, (iii) their professions' side that should be developed.